Youth Perceptions of Seren Taun Sacred Values in the Digital Age: A Scoping Review - Ainy Rahmatunisa; Mirna Nur Alia Abdullah; Fajar Nugraha Asyahidda (SOSIOEDUKASI, 2026)
The Seren Taun tradition, organised by the Sunda Wiwitan indigenous community in Cigugur Village, is one of the traditions that has managed to survive amidst social change. Since the advent of digital technology, the way in which the younger generation perceives tradition has shifted, from passive recipients to active agents in interpreting and representing cultural values. The aim of this study is to examine how the younger generation interprets the values of the Seren Taun tradition and how digital technology influences this process of meaning-making. The approach used is qualitative, employing a scoping review method to map and synthesise relevant research findings. Findings were obtained from the Scopus and Publish or Perish databases, comprising a total of 25 national and international articles analysed using thematic analysis techniques. The research results reveal that the younger generation actively interprets and represents traditional values through digital media, which simultaneously opens up space for the expansion of meaning and the risk of simplifying sacred values. The sustainability of traditions no longer depends solely on the preservation of cultural practices, but on the ability of the younger generation to negotiate and adapt cultural meanings amidst digital dynamics; thus, the integration of cultural practices, education, and digital media becomes a crucial strategy in maintaining the relevance of traditions amidst ever-evolving social change.